Flood hazard assessment in large plain basins with a scarce slope in the Pampean Plain, Argentina - Borzi, Guido Esteban (2021)
Floods are one of the most common natural phenomena and represent a serious hazard when they affect human activities. Structural measures are commonly used to mitigate them; however, these do not always give good results, mainly in plain areas with scarce slope. In this sense, the generation of a flood hazard map contributes to adequate hazard management and disaster prevention. The aim of this work is to evaluate the flood hazard areas in hydrological plain basins with scarce slope, taking as a case study the Samborombón river basin located in the Pampean Plain, Argentina. For this, a flood hazard map was made based on the analytical hierarchy process and using a GIS, taking into account physical aspects of the terrain, observations, and field measurements. Likewise, the map was validated using satellite images and the inhabitants in danger in the basin were quantified. The results show that the flood hazard areas correspond mainly to the floodplain of rivers and tributaries, while the main and secondary divide zones have low flood hazard sectors. On the other hand, numerous urban settlements were identified within flood hazard areas, these being urban settlements in the vicinity of old urban centers and new gated communities with high value homes, quantifying 1961 inhabitants at flood hazard and showing poor territorial planning. The methodology proposed gives to the management agencies the possibility of generating land use maps, as well as designing mitigation and contingency plans after a large rainfall event.